A Speech Act Analysis of the Language of Protest in 2020 Endsars Protest in Nigeria - Eze, Cyprian Chidozie; Chukwuezi, Emmanuel Eziaku; Umelo, Ngozi Jovita N.; Umeh, Ifeyinwa J. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study evaluates the language of protest which has been examined using different approaches. Certain linguistic features such as claim, threat, demand, appeal and dissatisfaction have been reported. However, it appears that similar studies are yet ti be done in Nigeria despite constant occurrence of protest in the country. The present study examines the language of protests in Nigeria using the 2020 EndSars protest. The data for the study were collected from social media and reputable news platforms, 36 data were gathered and grouped under their linguistic features. This research reveals that more demands were made during the course of the 2020 EndSars protest. Both quantitative and qualitative methods of findings from the analysis were employed. The statements of the protest were explicitly explained and the percentage for each linguistics feature was drawn and presented in tables.